2001
DOI: 10.1161/01.atv.21.5.791
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A 2A Receptor Stimulation Reduces Inflammation and Neointimal Growth in a Murine Carotid Ligation Model

Abstract: Abstract-Endothelial activation and leukocyte recruitment are early events in atherosclerosis and the vascular response to injury. Adenosine has anti-inflammatory effects on leukocytes and endothelial cells mediated through its A 2A receptor. We tested the hypothesis that A 2A activation would reduce inflammation and neointimal formation in a murine carotid ligation model. Before injury, mice were randomized to a 7-day subcutaneous infusion of a specific A 2A receptor agonist (ATL-146e, 0.004 g/kg per minute),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 46 publications
5
78
1
Order By: Relevance
“…In ischemia reperfusion models, the use of A 2A receptor agonists resulted in a decrease in macrophage activation and adhesion molecular expression on endothelial cells, blockage of endothelial-neutrophil interactions, and attenuation of vascular derangement (11,12,(17)(18)(19)(20)(21). The administration of the A 2A receptors agonist CGS-21680 has been shown to ameliorate lung injury in animal models of ischemia and reperfusion (12,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ischemia reperfusion models, the use of A 2A receptor agonists resulted in a decrease in macrophage activation and adhesion molecular expression on endothelial cells, blockage of endothelial-neutrophil interactions, and attenuation of vascular derangement (11,12,(17)(18)(19)(20)(21). The administration of the A 2A receptors agonist CGS-21680 has been shown to ameliorate lung injury in animal models of ischemia and reperfusion (12,17).…”
Section: Discussionmentioning
confidence: 99%
“…The A 2A R expressed on leukocytes and lung displays high affinity for adenosine (8). Several studies have shown that activation of A 2A receptor is protective against ischemia/reperfusion injury by decreasing the expression of endothelial adhesion molecules and the production of cytokines and reactive oxygen species (17)(18)(19)(20)(21). We thus hypothesized that a pharmacologic intervention with an A 2A R agonist protects the lung from injury in a two-hit model of HSR followed by mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, adenosine is a potent anti-inflammatory agent with A 2A Rs triggering BOFF^signals in activated immune cells, which constitutes one of the most fundamental and immediate tissue-protecting mechanisms (reviewed in [295,296]). A 2A R agonists were even named Bthe most potent anti-inflammatory drug known to mankind.^Ac-cordingly, activation of A 2A Rs has been shown to confer a robust protection against tissue damage from ischemiaYreperfusion injury in different organ such as heart [297Y299], blood vessels [300], kidney [301,302], liver [303,304], lung [305,306], joints [307], skin [308,309], and even in the spinal cord [310,311] and in the brain following hemorrhage [312] or acute infection [313]. Thus, it is the activation (rather the blockade) of A 2A Rs that confers protection against damage triggered by inflammation in peripheral tissues, precisely the opposite of what is observed in the damaged adult brain.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
“…Interestingly, an in vivo model of smooth muscle cell proliferation revealed that an A2 receptor agonist, 2-octynyladenosine, inhibited neointima formation (8). Furthermore, it has been reported that A2aAR activation reduces neointimal formation in a carotid ligation injury model (9). Adenosine receptors also play a major role in several inflammation-associated processes by inhibiting immune activation and preventing excessive tissue damage.…”
Section: Inflammation ͉ Cxcr4mentioning
confidence: 99%